Handbook of physics in medicine and biology - Splinter, Robert (CRC Press, 2010)
Presents a quantitative physical description of different aspects of cellular and organ performance and methods used to measure these functions. This title covers the physics necessary to understand the theoretical and practical basis for development of diagnostic and therapeutic tools.